A study on an observation of the road accident in Kuching / Muhammad Fuad Jobli ... [et. al] - Pali, Stacey Kieth; Akon, Norlida; Buang, Mohamad Zainal; Julaihi, Mohamad Hanifhaswandy; Jobli, Muhammad Fuad (2004)
Road accident always happens around the globe. The numbers of road accident keep increasing every day, every hour and every minute. Based on the research from Malaysia Road Safety Council the research made by ESCAP was based on every 10,000 vehicle and from this 248.3 accident cause death of 8.28 in Malaysia. The significant of this study is to identify the factor of road accident among the road user in Kuching. Through this significant of the study, we can relate to this study that is Road Condition, Attitude and Existing Laws.